The Effect of Different Substrates of Spawing and Hatching of Zebrafish Pink Danio (Brachydanio rerio) - Ade Helfris Marchaka; Nuraini Nuraini; Netti Aryani (Jurnal Akuakultur SEBATIN, 2021)
This study aims to determine the effect of different substrates on the spawning and hatching of Zebrafish Pink Danio (Brachydanio rerio), and to determine the best substrate for hatching Zebra Pink Danio eggs. This research was conducted from February to March 2020 at the Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Universitas Riau. The fish used were 24 Pink Danio broodfish (12 male and 12 female broods with an average length of 3.77 cm for males and 3.87 cm for females. The method used was a completely randomized design method RAL) with 4 treatments with 3 replications, while the treatments were SO (control), SH (Hydrilla), STR (Tali raffia), SI (Ijuk). The results of this study concluded that different substrates had an effect on fish spawning and hatching. Zebra Pink Danio uses a substrate, natural spawning using a substrate such as Hydrilla gives the best results with an average number of eggs 288 eggs, fertilization rate (FR) of 92.58%, hatchability rate of eggs (HR) of 91.97% , and the 10-day larval survival rate was 91.26%. The water quality during the study was in the optimal range for the spawning of Zebrafish Pink Danio, such as temperatures ranging from 29.5-31.20C, pH 6-7.3 and dissolved oxygen. (DO) 4-5 mg / L.